Reconfiguring education and research in the European Higher Education Area (Revista Lusófona de Educação, 2019)
The objective of this paper is to contribute to the understanding of the reconfigurations of education and research within the European Higher Education Area. While higher education systems and institutions are pointed out as key to competitively positioning Europe in the global context, the articulations between education, research and innovation are reconfigured. Based on discourse analysis, the articulations between nodal points - education, research and innovation - associated with the discourses on mobility and employability, made visible the weight of innovation promoted by economic policy drivers. The analysis challenges the relevance attributed to innovation and its major economic prospects as it hinders the broader educational and social potential of the political achievements of European Higher Education Area related to mobility and employability.Keywords: education; research; innovation; European higher education area